CHULA Beyond Leading Changes: a Capacity Building Program for Campus Sustainability at Chulalongkorn University - Inkarojrit, Vorapat; Chanchamroen, Supaporn; Hirunsuthikul, Narin; Stitmannaithum, Boonchai; Limsuwan, Korb (Journal of Sustainability Perspectives, 2023)
Capacity building for campus sustainability has been recognized as a process of strengthening the university stakeholders’ skills to minimize the negative impacts of current crises and emerging challenges. While many universities emphasize capacity building through research and education activities, most, if not all, neglect activities for non-academic staff. Without the necessary capacity, the universities might not be able to realize their development plans. To address this issue, Chulalongkorn University developed a capacity building program called “Beyond Leading Changes” in 2021 which consists of three modules. The first aims to provide SDGs knowledge and raise awareness on the local and global challenges. The second focuses on the design thinking process in which participants were asked to empathize, define, and ideate potential solutions to sustainability problems. The last module utilizes the project-based leaning approach in which the skills were developed through engaging projects set around real-world problems. 70 supporting staff from various units completed the program which resulted in many interesting pilot projects that cover a wide range of issues. Nevertheless, the challenge remains to make the program more accessible and inclusive.